Novel p38α MAP kinase inhibitors identified from yoctoReactor DNA-encoded small molecule library12. Issue 7 (28th June 2016) - Petersen, L. K.; Blakskjær, P.; Chaikuad, A.; Christensen, A. B.; Dietvorst, J.; Holmkvist, J.; Knapp, S.; Kořínek, M.; Larsen, L. K.; Pedersen, A. E.; Röhm, S.; Sløk, F. A.; et al.
Abstract : A DNA-encoded small-molecule library was prepared using yoctoReactor technology followed by binder trap enrichment to identify selective inhibitors with nanomolar potencies against p38α MAP kinase. Abstract : A highly specific and potent (7 nM cellular IC50 ) inhibitor of p38α kinase was identified directly from a 12.6 million membered DNA-encoded small molecule library. This was achieved using the high fidelity yoctoReactor technology (yR) for preparing the DNA-encoded library, and a homogeneous screening technique – the binder trap enrichment technology (BTE). Although structurally atypical to other kinase blockers, this inhibitor was found by X-ray crystallography to interact with the ATP binding site and provide strong distortion of the P-loop. Remarkably, it assumed an alternative binding mode as it lacks key features of known kinase inhibitors such as typical hinge binding motifs. Interestingly, the inhibitor bound assuming a canonical type-II ('DFG-out') binding mode by forming hinge hydrogen bonds with the backbone, showed excellent shape complementarity, and formed a number of specific polar interactions. Moreover, the crystal structure showed, that although buried in the p38α active site, the original DNA attachment point of the compound was accessible through a channel created by the distorted P-loop conformation. This study demonstrates the usability of DNA-encoded library technologies for identifying novel chemical matter with alternative binding modes to provide a good starting point for drug development.